184 Temporospatial Effects of Endothelium Specific Inhibition of Shc Homology 2 -containing Inositol 5´ Phosphatase 2 on Nitric Oxide Bioavailability and Whole Body Insulin Sensitivity. (31st May 2014) - Gage, Matthew; Viswambharan, Hema; Sukumar, Piruthivi; Cubbon, Richard; Imrie, Helen; Galloway, Stacey; Abbas, Afroze; Yuldasheva, Nadira; Smith, Jessica; Skromna, Anna; Grant, Peter; Gatenby, Victoria; et al.
Abstract : Introduction: Ageing is an important risk factor for diabetes and cardiovascular disease. Integrity of the endothelium plays a critical role in cardiovascular pathophysiology. Insulin signalling in endothelial cells modulates the generation of nitric oxide and reactive oxygen species. Although the vascular implications of endothelial insulin resistance are well understood, the effect of enhanced endothelial insulin signalling on whole body glucose regulation and vascular function remains poorly characterised. We therefore generated mice with downregulation of the negative regulator of insulin signalling; SHIP2 in endothelial cells, to investigate whether enhanced insulin signalling restricted to the endothelium modulates vascular function and whole body glucose regulation. Methods: We deleted exons 18–19 of the ship 2 gene using Cre-Lox technology under the control of the Tie2 promoter to generate a catalytically inactivate protein. Male mice heterozygous for the inactive protein (ECSHIP2KD) were compared with sex-matched littermate controls. Results: ECSHIPKD exhibited normal development. At 8 weeks of age ECSHIP2KD mice displayed increased glucose tolerance after glucose challenge (P = 0.03) and improved insulin sensitivity (P = 0.02) after insulin challenge compared to controls. Surprisingly however, by 40 weeks of age this phenotype was reversed; ECSHIP2KDmice revealed significant insulin resistance after insulin challenge (P = <0.05). Euglycemic hyperinsulinemic clamping confirmed whole body insulin resistance (decreased glucose infusion rate of 26% P < 0.05). In young mice ex vivo aortic vasomotor studies in both controls and ECSHIPKD revealed similar contractile responses to phenylephrine and displayed decreased contraction after insulin incubation. Both groups displayed increased contraction after NO synthase inhibitor LNMMA incubation. However, at 40 weeks old in ECSHIP2KD mice the vasodilatory aortic ring response to insulin was abolished (Emax controls 0.59 ± 0.04g vs 0.47 ± 0.03g P = 0.04, ECSHIP2KD 0.64 ± 0.04g vs 0.63 ± 0.06g P = 0.9) and ECSHIP2KD displayed no increase in contraction to LNMMA incubation (Emax controls 0.59 ± 0.04g vs 0.82 ± 0.08g P = 0.02, ECSHIP2KD0.64 ± 0.04g vs 0.69 ± 0.07g P = 00.5) indicating insulin resistance and lower basal nitric oxide (NO) production. Western blots experiments performed on cultured endothelial cells from 40 week old mice reveal significantly increased level of endothelial nitric oxide synthase (eNOS) but a lack of eNOS phosphorylation after stimulation with insulin. Resistance to activation by insulin was also confirmed through 14 C L-citrulline conversion assay. Conclusion: Downregulation of SHIP2 augments whole body glucose disposal in young mice but attenuates whole body glucose disposal in older mice, our data suggest this may be mediated by changes in nitric oxide bioavailability and identifies novel spatial and temporal specific affects of the lipid phosphatase SHIP2.